Care Home Stories Aging, Disability, and Long-Term Residential Care - Chivers, Sally; Kriebernegg, Ulla (Aging Studies, 2017)
Institutional care for seniors offers a cultural repository for fears and hopes about an aging population. Although enormous changes have occurred in how institutional care is structured, the legacies of the poor house still persist, creating panicked views of the nursing home as a dreaded fate. The paradoxical nature of a space meant to be both hospital and home offers up critical tensions for examination by age studies scholars. The essays in this book challenge stereotypes of institutional care for older adults, illustrate the changes that have occurred over time, and illuminate the continuities in the stories we tell about nursing homes.